(untitled) (Fiep Bulletin - online, 2014)
This paper is an analysis of scientific production of Laboratory, Movement and Media in Physical Education (LCMMEF) of the CEFD/UFSM. The purposes of this study was to identify the works of post-graduation during the period from 1991to 2004 in the LCMMEF; to verify the interdisciplinarity approaches in these works, and to verify whether the scientific output until 2004 support the three new research lines proposed for the rearrangement of the area. The study found that is necessary to amplify the discussion about the relations between Physical Education and Media that increased with the creation of law new and rearrangement of the curricula of the Physical Education Courses. The research also found that some papers of LCMMEF has make a profound study about the relation between Media and Physical Education/Sport. But, is important to create new strategics of relations interdisciplinarity to support others studies in area porposal of the LCMMEF, based in comprehension of media like pedagogical instrument that the Physical Education can to use for to intervence in society and not how a simple instrument of view of world. This aspect is the difference and the importance to discuss media in differents context of action of Physical Education/Sport.